THE IMPLEMENTATION OF INDONESIA’S PUBLIC POLICY TO IMMIGRATION SELECTIVE POLICY BASED ON LAW NO. 6 OF 2011 - Muhammad Azzam Alfarizi (Polteknik Imigrasi, 2018)
The inherent right of the individual is an affirmation that human beings must be treated properly and civilized and must be respected, as the sounding of the second precept is: